Aplicación móvil para promover estilos de vida saludables y realizar seguimiento de hábitos (2024)
This thesis introduces the development of a mobile application designed to promote healthy lifestyles and facilitate the tracking of habits related to health and well-being. In the context of the growing concern for health and well-being, the project focused on addressing issues related to unhealthy lifestyle habits that affect a significant portion of the population.